2007
DOI: 10.3758/bf03193505
|View full text |Cite
|
Sign up to set email alerts
|

Short-term recognition memory for serial order and timing

Abstract: 1724Numerous contemporary models of memory are dedicated to explaining short-term order memory, and in doing so adopt a variety of assumptions to explain people's ability to maintain and recall the order of items or events in a sequence over the short term. In some models, such as chaining models (e.g., Lewandowsky & Murdock, 1989;Murdock, 1995) and ordinal models (e.g., Farrell & Lewandowsky, 2002;Page & Norris, 1998), ordering is assumed to follow from the relationships between items (associations and relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 59 publications
6
40
0
Order By: Relevance
“…Although we leave it as a topic for future investigation, we have no reason to believe that the kind of process we have described for recognition over short timescales might not apply to these kinds of extended events as well. As a longer event, e.g., a sentence or sequence of items (e.g., Farrell & McLaughlin, 2007), unfolds over time, aspects of the event-the incoming words, prosody, and momentary understanding of the semantics of the sentence-join those features already present in working memory and could be used to probe memory in exactly the way our model describes. The dynamics of familiarity are influenced by what features are present in the probe over time.…”
Section: Extended Eventsmentioning
confidence: 99%
“…Although we leave it as a topic for future investigation, we have no reason to believe that the kind of process we have described for recognition over short timescales might not apply to these kinds of extended events as well. As a longer event, e.g., a sentence or sequence of items (e.g., Farrell & McLaughlin, 2007), unfolds over time, aspects of the event-the incoming words, prosody, and momentary understanding of the semantics of the sentence-join those features already present in working memory and could be used to probe memory in exactly the way our model describes. The dynamics of familiarity are influenced by what features are present in the probe over time.…”
Section: Extended Eventsmentioning
confidence: 99%
“…Accordingly, in an experiment that randomly intermixed unconstrained reconstruction trials with forward serial recall trials, and in which people were unaware of the type of test until after list presentation, isolation effects nonetheless selectively occurred with the former but not with the latter test. (In support of the notion that people can shift attention after encoding, Farrell & McLaughlin, 2007, reported a similarly selective use of time between two variants of a recognition test.) Thus, whenever forward serial retrieval is required, people will rely on the positional dimension at recall and thus do not show a temporal isolation effect (see Table 1), notwithstanding the fact that they have demonstrably encoded information about the temporal properties of the list.…”
Section: Simplementioning
confidence: 74%
“…Likewise, the absence of an isolation effect has been observed with both visual and auditory stimuli Parmentier et al, 2006), and it has been observed with single-item probed recall as well as with whole-report forward serial recall . Even with serial recognition, no isolation effects are observed under conditions that are thought to be most favorable to their emergence (e.g., because on some trials, participants are asked to retain timing information, which they are demonstrably able to do; Farrell & McLaughlin, 2007).…”
Section: Temporal Isolation Effects In Short-term Memorymentioning
confidence: 99%
“…An alternative approach is taken by Farrell and McLaughlin (2007), who found that serial recognition of items that were irregularly spaced in time during presentation was not affected by the temporal proximity of items, although temporal information was encoded as evidenced by participants' ability to perform a temporal recognition task. Along with other results (e.g.…”
Section: Discussionmentioning
confidence: 97%